Antioxidant effects of ryegrass phenolics in lamb liver and plasma. (30th October 2013) - López-Andrés, P.; Luciano, G.; Vasta, V.; Gibson, T. M.; Scerra, M.; Biondi, L.; Priolo, A.; Mueller-Harvey, I.
Abstract : Sixteen lambs were divided into two groups and fed two different diets. Eight lambs were stall-fed with a concentrate-based diet (C), and the remaining eight lambs were allowed to graze on Lolium perenne (G). The antioxidant status was measured in the liver and plasma samples before and after solid-phase extraction (SPE) to probe the antioxidant effects that grass phenolic compounds may have conferred onto the animal tissues. The liver and plasma samples from grass-fed lambs displayed a greater antioxidant capacity than the tissues from C lamb group, but only if samples had not been passed through SPE cartridges. Finally, the feed and animal tissues, which had been purified by SPE, were analysed by liquid chromatography combined with mass spectrometry (LC–MS) to identify phenolic compounds present in L. perenne and to evaluate the results from the antioxidant assays. It would appear that the improvement of the antioxidant capacity of lamb liver and plasma from lambs fed ryegrass was not related to the direct transfer of phenolic compounds from grass to the animal tissues.